RESPON PADI SAWAH PADA SISTEM BUDIDAYA SECARA MIXCROPPING DENGAN TANAMAN DUCKWEED - Donatus Kantur; Rupa Matheus (Partner, 2021)
The aim of the research was to find the effect of mixcropping system of rice and duckweed toward agronomy performance of rice. The treatments were tested: monoculture of rice (Pdmono), mixcropping rice with Lemna, Lemna planting 1 week before rice planting (PdLM1), mixcropping rice with Lemna, Lemna planting at rice planting (PdLM2), mixcropping rice with Lemna, Lemna planting 1 week after rice planting (PdLM3), mixcropping rice with Spirodela , Spirodela sp planting before 1 week rice planting (PdSd1), mixcropping rice with Spirodela, Spirodella planting at rice planting (PdSd1), mixcropping rice with Spirodela , Spirodela planting before 1 week rice planting (PdSd1), monoculture Lemna and monoculture Spirodela. The result showed that, cropping pattern not significant to plant height, number of tillers, percent of empty grain and 1000 grain weight compare to other variables, Cropping pattern PdLm3 resulted number of productive tillers and grain dry weight as higher compared to other cropping pattern.   Key Words: Response, Rice, Mixcropping system, Duckweed